The Development of Energy Efficiency Estimation System (EEES) for Sustainable Development: A Proposed Study. (November 2015) - Khairunnisa, A.R.; Yusof, M.Z.M.; Salleh, M.N.M.; Leman, A.M.
Abstract: In the modern era of globalization, energy is regarded as something precious. Thus, energy efficiency (EE) and cost effectiveness are key factors in maintaining economic growth. EE also educates consumers on ways to use energy efficiently and therefore, reduces energy consumption. In Malaysia, domestic sector is the third largest contributor to energy usage. The purpose of this study is to review EE practices and applications in residential buildings in order to raise awareness on smart energy consumption. In the preliminary stage of this study, consumers estimate their monthly energy consumption of their electrical appliances by using Quality Function Deployment (QFD) approach. QFD approach focuses on consumers' opinion of electrical appliances good and beneficial functions. Selection of residence was made between medium and affordable cost residential areas in Johor. Databases for energy relating to electrical appliances were developed based on the data obtained from the relevant ministry and agencies such as KeTTHA, Energy Commission and TNB. Energy Efficiency Estimation System (EEES) is being developed to help consumers estimate the amount of energy being used daily, which will help consumers to use energy more efficiently. EE indirectly helps reduce the effect on environment especially the greenhouse gases. The promotion of EE and independence from the non-renewable energy source is important in ensuring a sustainable development.